Single-molecule imaging reveals modulation of cell wall synthesis dynamics in live bacterial cells - Timothy K. Lee (Nature Portfolio, 2016)
The bacterial cell wall is important for cell shape and stability, but how the activities of the biosynthetic machinery are coordinated are not clear. Here the authors use single-molecule imaging and chemical perturbations to determine factors that affect the localization dynamics of penicillin-binding proteins (PBP)1A and PBP1B.